A non-canonical BRD9-containing BAF chromatin remodeling complex regulates naive pluripotency in mouse embryonic stem cells. Issue 1 (December 2018) - Gatchalian, Jovylyn; Malik, Shivani; Ho, Josephine; Lee, Dong-Sung; Kelso, Timothy; Shokhirev, Maxim; Dixon, Jesse; Hargreaves, Diana
Abstract The role of individual subunits in the targeting and function of the mammalian BRG1-associated factors (BAF) complex in embryonic stem cell (ESC) pluripotency maintenance has not yet been elucidated. Here we find that the Bromodomain containing protein 9 (BRD9) and Glioma tumor suppressor candidate region gene 1 (GLTSCR1) or its paralog GLTSCR1-like (GLTSCR1L) define a smaller, non-canonical BAF complex (GBAF complex) in mouse ESCs that is distinct from the canonical ESC BAF complex (esBAF). GBAF and esBAF complexes are targeted to different genomic features, with GBAF co-localizing with key regulators of naive pluripotency, which is consistent with its specific function in maintaining naive pluripotency gene expression. BRD9 interacts with BRD4 in a bromodomain-dependent fashion, which leads to the recruitment of GBAF complexes to chromatin, explaining the functional similarity between these epigenetic regulators. Together, our results highlight the biological importance of BAF complex heterogeneity in maintaining the transcriptional network of pluripotency. The BAF complex is a multi-subunit chromatin remodeling complex that plays important roles in transcription regulation. Here the authors provide evidence that BRD9 and GLTSCR1/BICRA or its paralog GLTSCR1-like/BICRAL define a non-canonical BAF complex that regulates naive pluripotency in mouse embryonic stem cells.